Considerations about two cases of sarcoma endometrial (uterine estromatosis) - Ramírez A., Graciela (2015)
It has presented two cases of endometrial sarcoma so far not been reported among us, to our knowledge. The histological picture of our cases is common to both. We believe this is a cancer that originates in endometrial stromal cells and malignant consider of its invasive and metastatic capacity. We consider appropriate the term Endometrial Sarcoma because it expresses the malignant nature of the lesion, its histogenesis and place of origin. We wish to draw attention to this entity with histologic features and very private clinics, separating adenomyosis and uterine stromal sarcoma no origin, for better recognition by the pathologist and institution of appropriate therapy.